(untitled) (Journal of Computational Mathematics, 2018)
This paper is devoted to the study of a nonlinear evolution eddy current model of the type _t B(H)+∇ × (∇ × H) = 0 subject to homogeneous Dirichlet boundary conditions H × ν=0 and a given initial datum. Here, the magnetic properties of a soft ferromagnet are linked by a nonlinear material law described by B(H). We apply the backward Euler method for the time discretization and we derive the error estimates in suitable function spaces. The results depend on the nonlinearity of B(H).